Toolkit to capture diversity and drivers of food choice of a target population to identify entry points for novel food products and nutritional interventions - CGIAR Research Program on Rice (2020)
The toolkit has been successfully implemented in (1) the Philippines to assess the market potential of traditional "heirloom" rice with medium-high income consumers in Metro Manila; and (2) India to capture diversity and drivers of food choice of low-middle income households and their response to behavioral change communication.